Lithium ion battery electrolyte and lithium ion battery
By introducing composite additives of lithium methacrylate trifluoroborate and vinylene carbonate into the lithium-ion battery electrolyte, and regulating the components of lithium salts and organic solvents, the problem of insufficient performance of lithium-ion batteries at extreme temperatures is solved, efficient high-temperature and low-temperature performance improvements are achieved, and the application range of batteries is expanded.
Patent Information
- Application Number
- CN202411716705.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-18
AI Technical Summary
The performance of existing lithium-ion batteries has significantly decreased in extreme temperature environments, especially under low or high temperature conditions. The ionic conductivity, chemical and thermal stability and electrochemical stability of the batteries are insufficient, limiting their application range.
The composite additive formed by introducing lithium methacrylate trifluoroborate and vinylene carbonate into the lithium-ion battery electrolyte, and the high and low temperature performance of the battery is improved by regulating the components of lithium salts and organic solvents.
The performance of lithium-ion batteries at extreme temperatures has been significantly improved, including the improvement of capacity retention and cycle number at 55°C, as well as the improvement of low-temperature cycle performance and conductivity at -20°C and -40°C, extending the cycle life of the battery and expanding its application range.
Smart Images

Figure CN119650849A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium ion battery electrolyte and a lithium ion battery. Background Art
[0002] In modern energy storage technology, lithium-ion batteries have become one of the most widely used rechargeable batteries due to their high energy density, long cycle life and low self-discharge rate. With the rapid development of electronic devices and electric vehicles, the performance requirements of lithium-ion batteries are becoming higher and higher, especially in applications under extreme temperature environments. However, the performance of traditional lithium-ion batteries will significantly decrease under low or high temperature conditions, which limits their application in a wider range of fields.
[0003] To solve this problem, researchers have been exploring lithium-ion battery electrolytes that can adapt to a wide temperature range. An ideal electrolyte should have the following properties: excellent ionic conductivity at low temperatures to ensure the rapid charge and discharge capabilities of the battery; sufficient chemical and thermal stability at high temperatures to prevent electrolyte decomposition and battery performance degradation. In addition, the electrolyte should also have a good electrochemical stability window to support the use of high-voltage cathode materials, thereby increasing the energy density of the battery.
[0004] The Chinese patent application with application publication number CN115197259A, which was applied for and published on October 18, 2022, discloses an organic alkali metal trifluoroborate salt containing an unsaturated bond, and a preparation method and application thereof. The organic alkali metal trifluoroborate salt contains an unsaturated bond, an ester and a trifluoroboric acid group (for example: lithium methacrylate trifluoroborate). While exerting the structural function of MBF4 (such as LiBF4), it can also assist in the formation of an SEI film and perform a function similar to that of VC. When 1% lithium methacrylate trifluoroborate is added to the electrolyte, the battery capacity remains above 87% after 65 cycles at 55°C.
[0005] However, the above electrolytes are still limited in improving the high-temperature cycle performance of lithium-ion batteries and reducing the impedance of battery cells. In addition, for electrolytes formed by carbonate-based organic solvents, the low-temperature conductivity and low-temperature cycle performance of the battery are still poor. Summary of the invention
[0006] The object of the present invention is to provide a lithium ion battery electrolyte to solve the problem that the lithium ion battery constructed with the existing electrolyte has poor high temperature performance or low temperature performance.
[0007] The second object of the present invention is to provide a lithium ion battery to solve the problem of poor high temperature performance or low temperature performance of existing lithium ion batteries.
[0008] In order to solve the above technical problems, the technical solution of the lithium ion battery electrolyte of the present invention is:
[0009] A lithium ion battery electrolyte comprises an organic solvent, a lithium salt and a composite additive, wherein the composite additive comprises vinylene carbonate and lithium trifluoroborate methacrylate in a mass ratio of 1: (0.5-1).
[0010] The present invention improves the prior art and provides a lithium ion battery electrolyte. By introducing a composite additive formed by lithium methacrylate trifluoroborate (LiBF3-OOC-C(CH3)=CH2) and vinyl carbonate into the electrolyte, the high temperature performance or low temperature performance of the battery is improved. On the basis of adding the composite additive, the high temperature cycle performance of the lithium ion battery can be improved and the impedance of the battery cell can be reduced by selecting a specific lithium salt. The low temperature cycle performance and low temperature conductivity of the battery can also be improved by regulating the components of the organic solvent. The performance requirements of the lithium ion battery at different extreme temperatures can be adapted to meet the needs of future energy storage systems. The present invention has important scientific significance and practical application value for promoting the development of energy storage technology and expanding the application scope of lithium ion batteries.
[0011] In order to further improve the high and low temperature performance of the ion battery, preferably, the addition amount of the composite additive in the lithium ion battery electrolyte is 1.5-2%.
[0012] In order to further improve the high temperature performance of the lithium ion battery, preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, and the concentration of the lithium salt is 1 to 1.2 mol / L.
[0013] In order to further improve the low temperature performance of the lithium ion battery, preferably, the organic solvent is selected from two or more of ethylene carbonate, ethyl methyl carbonate, propylene carbonate, ethyl acetate, ethylene glycol dimethyl ether, and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether.
[0014] In order to further improve the high and low temperature performance, preferably, when the organic solvent includes ethylene carbonate, ethyl methyl carbonate and propylene carbonate, the mass ratio of ethylene carbonate, ethyl methyl carbonate and propylene carbonate is (1-2):(5-6):(2-3).
[0015] In order to further improve the high temperature cycle performance of the battery, obtain a high temperature electrolyte suitable for high temperature (55°C), and reduce the battery impedance, preferably, the electrolyte is a high temperature electrolyte, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentrations of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are (0.7-0.9) mol / L and (0.1-0.2) mol / L, respectively. This two-component composite lithium salt can further improve the high temperature cycle performance of the battery, and the number of cycles can reach more than 1,000 when the capacity retention rate is 80% at 55°C.
[0016] In order to further improve the high temperature cycle performance of the battery, preferably, the lithium salt is composed of (0.7-0.8) mol / L lithium hexafluorophosphate, (0.1-0.2) mol / L lithium bis(fluorosulfonyl)imide and (0.1-0.2) mol / L lithium bis(trifluoromethanesulfonyl)imide. This three-component composite lithium salt can further improve the high temperature cycle performance of the battery, and the number of cycles can reach more than 1137 when the capacity retention rate is 80% at 55°C.
[0017] In order to further improve the low temperature performance of lithium ion batteries, a low temperature electrolyte suitable for low temperature is obtained. Preferably, the electrolyte is a low temperature electrolyte, and the organic solvent includes ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of (1-2): (5-6): (2-3): (1-2); or includes ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethyl acetate in a mass ratio of (1-2): (5-6): (2-3): (1-2). Compared with the three-component carbonate organic solvent formed by ethylene carbonate, ethyl methyl carbonate and propylene carbonate, the four-component organic solvent can further improve the low temperature cycle performance. The capacity retention rate of the electrolyte of the three-component organic solvent after 50 cycles at a low temperature of -20°C is 40-45%, while the capacity retention rate of the electrolyte of the four-component organic solvent can reach more than 92%.
[0018] In order to further improve the low-temperature conductivity and low-temperature viscosity of lithium-ion batteries at -40°C, and improve the battery capacity retention rate of discharge at -40°C, preferably, the electrolyte is a low-temperature electrolyte, and the organic solvent includes ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether in a mass ratio of (5-6): (5-6). The electrolyte formed by the organic solution of this component has a conductivity of 2.72mS / cm at -40°C, a viscosity of 7.62mPa.s at -40°C, and a battery capacity retention rate of 80.1% at -40°C.
[0019] The technical solution of the lithium ion battery of the present invention is:
[0020] A lithium ion battery comprises the lithium ion battery electrolyte.
[0021] The lithium ion battery provided by the present invention adopts the lithium ion battery electrolyte, and on the basis of introducing a composite additive formed by lithium trifluoroborate methacrylate (LiBF3-OOC-C(CH3)=CH2) and vinylene carbonate into the electrolyte, the high temperature performance and cell impedance of the lithium ion battery can be regulated, or the low temperature cycle performance and low temperature conductivity can be regulated by selecting a specific lithium salt or regulating the components of the organic solvent, so as to adapt to the performance requirements of the lithium ion battery at different extreme temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The results of the cell impedance test of lithium-ion batteries prepared with electrolytes of different formula compositions;
[0023] Figure 2 This is a state diagram of electrolytes with different formulations at -40°C. DETAILED DESCRIPTION
[0024] The technical concept of the lithium ion battery electrolyte of the present invention is as follows:
[0025] The present invention forms a composite additive by compounding vinylene carbonate and lithium methacrylate trifluoroborate. On the basis of introducing the composite additive into an electrolyte, the high temperature performance or low temperature performance of a lithium ion battery can be improved by regulating the lithium salt component and the organic solvent component in the electrolyte. On the basis of introducing the composite additive into the electrolyte, the lithium salt component is regulated so that the number of cycles of the battery can reach more than 830 when the capacity retention rate of the battery is 80% at 55° C., and the organic solvent component is regulated so that the capacity retention rate of the battery after 50 cycles at -20° C. reaches more than 92%, thereby significantly improving the performance of the lithium ion battery at extreme temperatures and meeting the needs of future energy storage systems.
[0026] In a specific embodiment, the preparation method of lithium methacrylate trifluoroborate is: firstly mix lithium methacrylate and an organic solution, then introduce BF3 gas for reaction, the reaction temperature is 0 to 5°C, the reaction time is 2 to 4 hours, after the reaction is completed, vacuum distillation is performed to concentrate and precipitate crystals, and then filtering and drying are performed to obtain the product.
[0027] The lithium ion battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet, and a PP separator. The positive electrode sheet comprises a lithium iron phosphate positive electrode active material, a conductive agent, and a binder. The mass ratio of the lithium iron phosphate positive electrode active material, the conductive agent, and the binder is (96-98): (1-2): (1-2). The surface density of the positive electrode sheet is 180-200 g / m 2The negative electrode sheet comprises a graphite negative electrode active material, a conductive agent, carboxymethyl cellulose and styrene-butadiene rubber, wherein the mass ratio of the graphite negative electrode active material, the conductive agent, carboxymethyl cellulose and styrene-butadiene rubber is (95-97):(1-2):(1-1.35):(1-1.65), and the surface density of the negative electrode sheet is 84-100 g / m 2 .
[0028] It is understandable that the additives include flame retardants, viscosity modifiers, ionic liquids and polymer thickeners, and different types of additives can be selected based on different performance requirements of lithium-ion batteries.
[0029] The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.
[0030] 1. Specific embodiments of the lithium-ion battery electrolyte of the present invention
[0031] The preparation method of the additive lithium trifluoroborate methacrylate LiBF3-OOC-C(CH3)=CH2 used in the lithium ion battery electrolyte of the present invention is as follows:
[0032] Add 100g of lithium methacrylate to the ether solvent, then slowly introduce 73.68g of BF3 gas into it, control the reaction temperature to 0-5°C, react for 2 hours, wait until the solid is completely dissolved, the solution is clear, and the reaction is finished; distill and concentrate under reduced pressure at 30°C, after crystals are precipitated, cool to -30°C, filter and collect the precipitated crystals, and dry at 50°C to obtain lithium methacrylate trifluoroborate LiBF3-OOC-C(CH3)=CH2, recorded as LiBF3R. The reaction equation is as follows:
[0033]
[0034] The formula composition of the lithium ion battery electrolyte of the present invention is shown in Table 1.
[0035] Table 1 Lithium-ion battery electrolyte formula composition
[0036]
[0037]
[0038] The lithium ion battery electrolyte of Example 1 is composed of an organic solvent, a lithium salt and a composite additive with a mass fraction of 2%, wherein the organic solvent is composed of ethylene carbonate, ethyl methyl carbonate and propylene carbonate in a mass ratio of 3:5:2, the lithium salt is 1 mol / L lithium hexafluorophosphate, and the composite additive is composed of 1% vinylene carbonate and 1% lithium methacrylate trifluoroborate.
[0039] The lithium ion battery electrolyte of Example 2 is composed of an organic solvent, a lithium salt and a composite additive with a mass fraction of 2%, wherein the organic solvent is composed of ethylene carbonate, ethyl methyl carbonate and propylene carbonate in a mass ratio of 3:5:2, the lithium salt is composed of 0.9 mol / L lithium hexafluorophosphate and 0.1 mol / L lithium bis(fluorosulfonyl)imide, and the composite additive is composed of 1% vinylene carbonate and 1% lithium methacrylate trifluoroborate.
[0040] The lithium ion battery electrolyte of Example 3 is composed of an organic solvent, a lithium salt and a composite additive with a mass fraction of 2%, wherein the organic solvent is composed of ethylene carbonate, ethyl methyl carbonate and propylene carbonate in a mass ratio of 3:5:2, the lithium salt is composed of 0.7 mol / L lithium hexafluorophosphate, 0.1 mol / L lithium bis(fluorosulfonyl)imide and 0.2 mol / L lithium bis(trifluoromethanesulfonyl)imide, and the composite additive is composed of 1% vinylene carbonate and 1% lithium trifluoroborate methacrylate.
[0041] The lithium ion battery electrolyte of Example 4 is composed of an organic solvent, a lithium salt and a composite additive with a mass fraction of 2%, wherein the organic solvent is composed of ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of 2:5:2:1, the lithium salt is composed of 0.9 mol / L lithium hexafluorophosphate and 0.1 mol / L lithium bis(fluorosulfonyl)imide, and the composite additive is composed of 1% vinylene carbonate and 1% lithium methacrylate trifluoroborate.
[0042] The lithium ion battery electrolyte of Example 5 is composed of an organic solvent, a lithium salt and a composite additive with a mass fraction of 2%, wherein the organic solvent is composed of ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether in a mass ratio of 1:1, the lithium salt is composed of 0.9 mol / L lithium hexafluorophosphate and 0.1 mol / L lithium bis(fluorosulfonyl)imide, and the composite additive is composed of 1% vinylene carbonate and 1% lithium trifluoroborate methacrylate.
[0043] The lithium ion battery electrolyte of Example 6 is composed of an organic solvent, a lithium salt and a composite additive with a mass fraction of 2%, wherein the organic solvent is composed of ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethyl acetate in a mass ratio of 3:5:2:1, the lithium salt is composed of 0.9 mol / L lithium hexafluorophosphate and 0.1 mol / L lithium bis(fluorosulfonyl)imide, and the composite additive is composed of 1% vinylene carbonate and 1% lithium methacrylate trifluoroborate.
[0044] The lithium ion battery electrolyte of Example 7 is composed of an organic solvent, a lithium salt and a composite additive with a mass fraction of 1.5%, wherein the organic solvent is composed of ethylene carbonate, ethyl methyl carbonate and propylene carbonate in a mass ratio of 3:5:2, the lithium salt is 1 mol / L lithium hexafluorophosphate, and the composite additive is composed of 1% vinylene carbonate and 0.5% lithium methacrylate trifluoroborate.
[0045] 2. Specific embodiments of the lithium-ion battery of the present invention
[0046] Example 8
[0047] The lithium-ion battery of this embodiment includes a positive electrode sheet, a negative electrode sheet, and a PP separator. The positive electrode sheet is a lithium iron phosphate positive electrode. The preparation method is as follows: lithium iron phosphate (LFP) is used as a positive electrode active material, and is uniformly mixed with a conductive agent activated carbon (SP) and a binder polyvinylidene fluoride (PVDF) in a nitrogen methyl pyrrolidone (NMP) solution. The mass ratio of LFP, SP and binder is 96:2:2 respectively, and then coated and pressed on a carbon-coated aluminum foil, with a surface density of 180g / m 2 The negative electrode sheet is a graphite electrode, and the preparation method is as follows: graphite (Gr) is used as the negative electrode active material, and is uniformly mixed with conductive agent activated carbon (SP), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in an aqueous solution, and the mass ratios of Gr, SP, CMC, and SBR are 95:2:1.35:1.65, respectively, and coated on a copper foil with a surface density of 84g / m 2 The lithium ion battery electrolyte of any one of Examples 1 to 7 is used for injection, and a soft-pack battery is obtained after formation and volume separation, namely a lithium ion battery.
[0048] 3. Experimental Examples
[0049] This experimental example illustrates the formulation composition of the lithium ion battery electrolyte of the present invention.
[0050] The electrochemical properties (gram capacity, first coulombic efficiency, high and low temperature cycle performance, discharge MAP test, and low temperature conductivity) of soft-pack batteries prepared with different electrolytes are tested and evaluated to screen the formula composition of the electrolyte.
[0051] High and low temperature cycle performance test method: put the battery cell into a high and low temperature test cabinet. The high temperature cycle performance is tested by performing high temperature 55℃, 1C / 1C charge and discharge cycles in the high and low temperature test cabinet, and recording the number of cycles when the SOH (battery health status) is 80%. The low temperature cycle performance is tested by performing low temperature -20℃, 0.5C / 0.5C charge and discharge cycles for 50 times in the high and low temperature test cabinet, and recording the capacity retention rate.
[0052] The screening formula composition of the electrolyte is shown in Table 2-3.
[0053] Table 2 Screening formula composition of electrolyte
[0054]
[0055]
[0056] Table 3 Screening formula composition of electrolyte II
[0057]
[0058] 1) Gram capacity and first coulombic efficiency test
[0059] The soft-pack batteries were prepared by using the electrolytes in Table 2-3 according to the method of Example 7. The gram capacity and the first coulombic efficiency of the batteries were tested by cyclic voltammetry. The test results are shown in Table 4.
[0060] Table 4 Battery gram capacity and first coulombic efficiency test results
[0061] Serial number Gram capacity (mAh / g) First coulombic efficiency (%) 1# 157.52 83.0 2# 157.90 84.5 3# 159.42 85.7 4# 165.43 83.8 5# 166.91 84.1 6# 151.32 83.2 7# 151.81 83.8 8# 157.94 85.2 9# 158.10 88.1 10# 157.28 87.6 11# 154.21 84.0 12# 155.70 84.3 13# 154.15 79.6 14# 155.12 84.9 15# 158.10 85.3 16# 159.23 85.4
[0062] It can be seen from Table 4 that adding different additives to the electrolyte has little effect on the gram capacity and the first coulombic efficiency of the battery. Among them, 8#-10# and 15#-16# show higher first coulombic efficiency (all greater than 85%), indicating that the first coulombic efficiency of the battery can be improved after lithium methacrylate trifluoroborate LiBF3R and vinylene carbonate (VC) are compounded with a specific ratio of organic solvent and lithium salt.
[0063] In addition, compared with 8#, the batteries prepared with 9#-10# electrolytes showed higher first coulombic efficiency, indicating that multi-component composite lithium salts can further improve the first efficiency of the battery, among which the binary composite lithium salt (9#) had the highest first efficiency.
[0064] 2) High temperature performance
[0065] Under the conditions of normal temperature 25°C / high temperature 55°C and 1C / 1C charge and discharge cycle, the number of cycles when the battery health condition (SOH) is 80% (that is, the capacity retention rate is 80%) is shown in Table 5.
[0066] Table 5 Cyclic performance test results
[0067]
[0068]
[0069] It can be seen from Table 5 that compared with adding VC or LiBF3R (1#-3#) alone, adding a composite additive of lithium trifluoroborate methacrylate LiBF3R and VC (8#-10#, 15#) to the electrolyte containing lithium salt can greatly improve the high temperature cycle performance of the battery.
[0070] Compared with 1#, the electrolyte using composite additives (8#-10#, 15#) has a cycle number increased by more than 127% when SOH is 80%, among which the cycle number of 8#-10# electrolyte has increased by more than 131%; compared with 2#, the cycle number has increased by more than 9.4%, which shows the unique role of the composite additive of LiBF3R and VC in improving the high-temperature cycle performance of the battery.
[0071] Compared with the compounding of VC and other additives (4#-7#, VC is compounded with lithium difluorooxalatoborate, lithium difluorophosphate, vinyl sulfate, and 1,3-propane sultone respectively), the composite additive of LiBF3R and VC described in the present invention increases the number of cycles by more than 10.2%. However, in the LFP / Gr system, when the content of LiBF3R is too high, there will be a certain degradation effect on both normal temperature and high temperature cycles.
[0072] However, in the electrolyte containing lithium tetrafluoroborate (11#), the high temperature cycle performance of the battery is extremely deteriorated, indicating the selectivity of the lithium salt component. The lithium salt of a specific component and the composite additive can be used together to further improve the high temperature cycle performance; and, on the basis of the use of composite additives, the multi-component composite lithium salt (9#-10#) can further improve the high temperature cycle performance of the battery compared to the single lithium salt (8#), among which the ternary composite lithium salt (10#) has the best high temperature performance; and, compared to the composite additive (8#) with a mass ratio of VC and LiBF3R of 1:1, the high temperature performance of the composite additive with a mass ratio of 1:0.5 is slightly worse (15#), and if the amount of LiBF3R added is further increased, the high temperature performance of the composite additive with a mass ratio of 1:2 will deteriorate (16#). 8#-10#, 15# formulas are the lithium ion battery electrolytes provided in Examples 1-3 and 7 of the present invention.
[0073] 3) Discharge MAP test
[0074] The battery prepared with 8#-10# electrolyte was subjected to 25℃ discharge MAP test, and the specific method was as follows: 1) Leave for 10 minutes, charge to 3.65V, 0.05C at 0.5C constant current and constant voltage; leave for 10 minutes, discharge to 2.0V at 0.5C constant current; 2) Repeat the above step 1) 3 times; 3) Leave for 10 minutes; charge to 3.65V, 0.05C at 0.5C constant current and constant voltage; leave for 60 minutes; discharge to the target power at 0.5C constant current, the target power = (1-target SOC)*0.5C discharge capacity; leave for 60 minutes; discharge at 3C constant current for 10S; leave for 40S; replenish power back to the target SOC at 0.5C constant current, that is, the cumulative power of pulse discharge and replenishment is zero; 4) Repeat the above step 3). Target power: SOC% (0%, 3%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%).
[0075] Figure 1 This is the DCR (DC resistance)-SOC curve obtained from the discharge MAP test. Figure 1 It can be seen that compared with 2#, the cell impedance of the battery prepared with 8#-10# electrolyte is significantly reduced, indicating that the introduction of the composite additive of LiBF3R and VC can greatly reduce the cell impedance; in addition, compared with 8#, the cell impedance of the battery prepared with 9#-10# electrolyte also decreases, indicating that the multi-component composite lithium salt can reduce the cell impedance, among which the ternary composite lithium salt has the most obvious effect on reducing the cell impedance.
[0076] 4) Low temperature performance
[0077] (1) Low temperature cycle performance
[0078] The SOH (capacity retention rate) of the batteries prepared with 2#, 8#-10#, and 12#-14# electrolytes was tested at -20°C and cycled 50 times. The test results are shown in Table 6.
[0079] Table 6 Low temperature cycle performance test results
[0080] Serial number SOH at -20℃ for 50 cycles 2# 32.1% 8# 32.3% 9# 44.0% 11# 41.2% 12# 92.5% 13# 94.9% 14# 93.6%
[0081] It can be seen from Table 6 that the cycle performance of the electrolyte (8#) with the addition of LiBF3R and VC composite additives and the electrolyte (2#) with only the addition of VC additives at low temperature (-20°C) does not change much; compared with 8#, the low-temperature cycle stability of the electrolytes formed by multi-component lithium salts (9#-10#) is improved to a certain extent, among which the low-temperature cyclability of the electrolyte (9#) formed by the two-component lithium salt is higher, indicating that the multi-component lithium salt has a certain effect on improving the low-temperature cycle performance.
[0082] The low-temperature cycle performance of the electrolyte containing ether or ethyl acetate (12#-14#) is greatly improved, and the SOH after 50 cycles at -20°C can reach more than 92%; among them, the electrolyte containing ethylene glycol dimethyl ether and tetrafluoropropyl ether (12#) has the best low-temperature cycle performance. This shows that on the basis of using composite additives, by introducing ether or ethyl acetate organic solvents into the carbonate system, or directly using ether organic solvents, the low-temperature cycle performance of the electrolyte can be greatly improved.
[0083] The battery capacity of the battery prepared with 12#-14# electrolytes after discharge at -40°C was tested, and the ratio to the battery capacity after charging at room temperature was calculated, and the battery capacity retention rate obtained after discharge at -40°C is shown in Table 7. As can be seen from Table 7, 13# electrolyte exhibits the best capacity retention rate at -40°C.
[0084] -40℃ discharge capacity test steps:
[0085] 1. Charge to 3.65V, 0.05C at 1C constant current and constant voltage at 25℃, leave for 5min, discharge to 2.0V at 1C, cycle for 3 weeks, and record the rated capacity C1;
[0086] 2. Charge to 3.65V, 0.05C at 1C constant current and constant voltage at 25℃, place in -40℃±2℃ environment for 20H, discharge to 2.0V at 1C, and record the capacity C2;
[0087] 3. Discharge capacity retention rate = C2 / C1 (judgment standard: calculated capacity is not less than 70% of the rated value).
[0088] Table 7 - Battery capacity retention rate at 40℃
[0089] Serial number Discharge capacity retention rate at -40℃ 12# 73.3% 13# 80.1% 14# 77.3%
[0090] (2) Low temperature conductivity
[0091] Conductivity is tested using a conductivity meter. Place the electrodes in the solution being tested, apply a certain potential across the electrodes, and then measure the current flowing between the plates. According to Ohm's law, resistance (R) is determined by voltage and current, and conductivity (G) is the reciprocal of resistance (R).
[0092] Since 2-8# are carbonate systems, they completely solidify at -40℃, and 9# electrolyte does not completely solidify at -40℃ and cannot be used in low temperature environments. At this time, conductivity testing cannot be performed, and 12#-14# electrolytes do not solidify. Figure 2 As shown, Figure 2 The electrolytes with different formulas are at -40℃. Figure 2From left to right in the figure are 8#, 9#, 12#-14# electrolytes. This shows that on the basis of using composite additives, by introducing ether or ethyl acetate organic solvents into the carbonate system, or directly using ether organic solvents, the low temperature performance of the electrolyte can be improved.
[0093] The low-temperature viscosity and low-temperature conductivity test results of 12#-14# electrolyte at -40°C are shown in Table 8.
[0094] Table 8 Low temperature viscosity and low temperature conductivity of electrolyte
[0095]
[0096] The test results in Table 8 confirm that the low-temperature conductivity and viscosity of the electrolyte can be improved by adjusting the ratio of organic solvents on the basis of using composite additives. The conductivity of the electrolyte at -40°C reaches 0.85mS / cm or more, and the viscosity reaches 7.5mPa.s or more; and, compared with the four-component organic solvent (12#) formed by ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether, the four-component organic solvent (14#) formed by ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethyl acetate is more conducive to the improvement of low-temperature conductivity, and exhibits lower viscosity and better electrolyte fluidity; in addition, the ether organic solvent (13#) formed by ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether exhibits the highest low-temperature conductivity and the lowest viscosity. Formulas 12#-14# are the lithium ion battery electrolytes provided by Examples 4-6 of the present invention.
[0097] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery electrolyte, characterized in that: The invention comprises an organic solvent, a lithium salt and a composite additive, wherein the composite additive comprises vinylene carbonate and lithium trifluoroborate methacrylate in a mass ratio of 1: (0.5-1).
2. The lithium ion battery electrolyte according to claim 1, characterized in that The addition amount of the composite additive in the lithium ion battery electrolyte is 1.5-2%.
3. The lithium ion battery electrolyte according to claim 1, characterized in that The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, and the concentration of the lithium salt is 1-1.2 mol / L.
4. The lithium ion battery electrolyte according to claim 1, characterized in that The organic solvent is selected from two or more of ethylene carbonate, ethyl methyl carbonate, propylene carbonate, ethyl acetate, ethylene glycol dimethyl ether, and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether.
5. The lithium ion battery electrolyte according to claim 4, characterized in that: When the organic solvent includes ethylene carbonate, ethyl methyl carbonate and propylene carbonate, the mass ratio of ethylene carbonate, ethyl methyl carbonate and propylene carbonate is (1-2):(5-6):(2-3).
6. The lithium ion battery electrolyte according to any one of claims 1 to 5, characterized in that: The electrolyte is a high-temperature electrolyte, and the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentrations of the lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are (0.7-0.9) mol / L and (0.1-0.2) mol / L, respectively.
7. The lithium ion battery electrolyte according to claim 6, characterized in that: The lithium salt consists of (0.7-0.8) mol / L lithium hexafluorophosphate, (0.1-0.2) mol / L lithium bis(fluorosulfonyl)imide and (0.1-0.2) mol / L lithium bis(trifluoromethanesulfonyl)imide.
8. The lithium ion battery electrolyte according to any one of claims 1 to 5, characterized in that: The electrolyte is a low-temperature electrolyte, and the organic solvent includes ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of (1-2):(5-6):(2-3):(1-2); or includes ethylene carbonate, ethyl methyl carbonate, propylene carbonate and ethyl acetate in a mass ratio of (1-2):(5-6):(2-3):(1-2).
9. The lithium ion battery electrolyte according to any one of claims 1 to 4, characterized in that: The electrolyte is a low-temperature electrolyte, and the organic solvent comprises ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether in a mass ratio of (5-6):(5-6).
10. A lithium ion battery, characterized in that: The invention comprises the lithium ion battery electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Trifluoroboric acid organic alkali metal salt containing unsaturated bonds as well as preparation method and application of trifluoroboric acid organic alkali metal salt
CN115197259A